When a Fresco Speaks: the Epigraphs in San Fiorenzo’s Church (Bastia di Mondovì – CN) - Barillari, Sonia Maura (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2022)
The epigraphs in the fresco cycle of the church of San Fiorenzo in Bastia (1466) are edited for the first time in this article. And for the first time, a classification of epigraphs according to their function is proposed here. Epigraphs can be subdivided into three groups with regard to their role in the figurative pattern: they can in fact fulfill a documentary, explanatory or narrative role in relation to the images with which they are associated. The epigraphs that we define as documentary have the purpose of attesting and making known information about the work (pictorial, sculptural, architectural, mosaic…) in which they are inserted. The inscriptions that we could call explanatory identify the figures they are associated with. The epigraphs with a ‘narrative’ function are more interesting: we have defined them in this way because they give voice to the characters with whom they are associated, who in this way converse with other painted figures or address their message to the beholder.
Keywords: San Fiorenzo’s church; medieval frescoes; epigraphs; painted dialogues; hagiography